Predisposition to depressive symptoms in patients with paranoid schizophrenia: constitutional-biological, socio-demographic factors and the debut of the disease - Kh. S. Zhyvago (Zaporožskij Medicinskij Žurnal)
Aim. To identify the constitutional-biological, socio-demographic (microsocial) and clinical-dynamic (the debut of the disease) factors of predisposition to the depressive symptoms development in patients with paranoid schizophrenia.